Differentiation of stereotypes: The influence of knowledge, affect, and national grouping - Beaux, Kay K. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Stereotypes of foreign countries were elicited from a sample of U. S. students in a form which provided (a) descriptive information for each country, and (b) a measure of cognitive complexity, or degree of trait differentiation among a group of countries. Fewer instances of consensus in stereotypy were found within countries of Latin America, as compared to nations of Western Europe; judgments of all Latin countries combined, however, showed much greater homogeneity, i.e. less trait differentiation between countries, than fourth European group. Further, in a comparison of the influence of knowledge about a country versus positive or negative regard for a country, the former factor was found to be of primary importance in determining the diversity of judgments made in a stereotyping task.